Can the Nasion-Mandibula Ratio Predict Obstructive Sleep Apnea in Patients With Retrognathia?. Issue 1 (March 2022) - van der Plas, Pleun P. J. M.; Koudstaal, Maarten J.; Pullens, Bas; Mathijssen, Irene M. J.; Wolvius, Eppo B.; Joosten, Koen F. M.
Introduction: Robin Sequence (RS) is characterized by retrognathia, glossoptosis, and upper airway obstruction (UAO). Nonetheless, the exact role of retrognathia in RS remains unclear. The aim of this study was to evaluate if measuring retrognathia could be of use next to the polysomnography (PSG) in the diagnosis of RS by differentiating RS patients and controls. Furthermore, this study endeavored to evaluate mandibular growth over time. Methods: A retrospective study was performed on RS patients without life-threatening UAO and controls. Mandibular length was assessed by using the Nasion-Mandibula Ratio (NMRatio) at the following three time points: 0 to 3 months, 1 year, and 4 years of age. Results: A total of 107 patients were included of whom 38 were diagnosed with RS. Thirty-two patients presented with clinical retrognathia but without obstructive sleep apnea (OSA), whilst 37 patients had an isolated cleft palate (CP). At 0 to 3 months, 1 year, and 4 years of age, significant higher NMRatios were found in RS patients compared to isolated CP patients, whilst no significant differences were found compared to retrognathia-only patients. Within RS patients, no significant differences were found between isolated versus non-isolated and invasively versus non-invasively treated patients. In all three patient groups, a significant decrease of the NMRatio was seen at the age of 4 years compared to 0 to 3 months and 1 year of age. Conclusions: Although the NMRatio differs between RS and isolated CP patients, a seemingly small mandible (in a-p direction) does not reflect functional outcomes in RS patients and a PSG should always be performed to confirm the diagnosis. Despite that mandibular length significantly increased after the first year of life, mandibular size of RS patients does not seem to reach values of normal infants. Accordingly, mandibular catch up growth, that is suggested to be typically present in RS patients, was not found by our study.